Pengembangan Identitas Usaha UMKM melalui Pelatihan Pembuatan Nomor Induk Berusaha (NIB) Berbasis Digital di Desa Nagasari, Kabupaten Bekasi - Wibowo, Setyo; Muis, Abdul; Rofieq, Ainur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Nagasari Village, Serang Baru District, Bekasi Regency, has many MSMEs (Micro, Small, and Medium Enterprises) that are growing and developing, but most of them have not utilized technology optimally. One of the main challenges is the lack of a clear business identity, such as a Business Identification Number (NIB), which limits local market access and development opportunities. This community service program aims to improve the understanding and ability of MSME actors in registering NIB digitally, so that they can strengthen their business identity. The method used is direct training through socialization sessions, interactive discussions, and technical assistance to MSME actors. The results of the community service show that MSME actors in Nagasari Village are able to understand the importance of NIB and have successfully implemented the online registration process. This program provides real benefits in the form of wider access to business legality, increased competitiveness, and MSME readiness to face technology-based markets.